Development of integrated daylighting and natural ventilation system for energy efficiency in buildings for the tropics / Salmah Ahmed - Ahmed, Salmah (Institute of Graduate Studies, UiTM, 2012)
Natural ventilation and daylighting are two passive strategies that can improve the indoor performance as well as reduce energy consumption in buildings. Both strategies when used appropriately increase indoor quality and comfort. In terms of energy costs, daylighting can significantly reduce artificial lighting as well as heat dissipated from the resulting fixtures while natural ventilation can minimize the need for air-conditioning. This research was conducted to develop an integrated system, which combined the daylighting and natural ventilation specifically for energy efficiency in buildings in the tropical countries like Malaysia.